Pengaruh Strategi Pembelajaran Tipe The Power of Two Terhadap Hasil Belajar IPS Siswa SD Negeri 3 Rajabasa Kota Bandar Lampung - Erzisa, Mella; Qomario, Qomario; Agung , Putry (Gayaku Publisher, 2023)
This study discusses the effect of the power of two strategy on social studies learning outcomes for students of SD Negeri 3 Rajabasa, Bandar Lampung City. This study aims to describe whether there is an effect of using the power of two strategy on social studies learning outcomes for SD Negeri 3 Rajabasa students in Bandar Lampung. The survey results of the researchers found that social studies learning outcomes for students were still low. The method used in this research is quantitative with a quasi-experimental method with a Pretest-Posttest Design with Noneequivalent Group. The population in this study was class V SD Negeri 3 Rajabasa, Bandar Lampung city. The research sample was 38 students. The sampling technique used purposive sampling technique. Data collection techniques using observation, testing, documentation, data analysis techniques and using the t-test. The results of this study indicate an increase in the learning outcomes of fifth grade students at SD Negeri 3 Rajabasa, Bandar Lampung city. This is shown by the results of the t-test (paired sample t test) which produces a sig value. 2 tailed < 0.05. From the posttest value of the control class and the posttest of the experimental class, it shows a large influence of 41% which is included in the sufficient category. Based on the results of the study, there is an influence of the power of two learning strategy on student social studies learning outcomes.